Development of Tourism in the Light of Contemporary Economic Concepts - Barbara MARCISZEWSKA (Communications of International Proceedings, 2022)
The diverse activities carried out by tourism sector subjects in domestic and international markets largely concern tangible and intangible public goods; however, these activities are not naturally compatible. Additionally, private tour operators have hidden goals—often short-term and particularistic—that frequently force public institutions involved in the organization of tourist services to adjust their activities. Compared with the institutional economics proposed by classical and neoclassical economists, the new institutional economics (NIE) focuses on mechanisms of institutions, which allow a more comprehensive study of contemporary economic and social processes. The aim of this article is to show the relationship between the functioning of tourism market subjects and NIE assumptions in social terms. Further, it aims to show the need for identifying relationships between the NIE theoretical framework and the phenomena and processes in tourism. Evolutionary development theory has been taken into account as a relevant framework for analyzing tourism product development. This research was based on critical literature analysis and participant observation in the tourism sector. Notably, the new perspective presented in this paper allows discernment of non-market phenomena and processes that accompany economic mechanisms.
Keywords: social aspects of tourism; new institutional economics; evolutionary development; feedback in tourism.